2019
DOI: 10.7717/peerj.7437
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits from global warming to the thermal biology and locomotor performance of an endangered Patagonian lizard

Abstract: Global warming can significantly affect many aspects of the biology of animal species, including their thermal physiology and physiological performance. Thermal performance curves provide a heuristic model to evaluate the impacts of temperature on the ecophysiology of ectotherms. When integrated with other thermal biology parameters, they can be used to predict the impacts of climate change on individual fitness and population viability. In this study, we combine holistic measures of thermal physiology and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
3
23
1
2
Order By: Relevance
“…At least a third (33%) of the recorded T e values were higher than the T pref during the warmest hours which increases the risk for these lizards of attaining near-lethal body temperatures close to their CT max . Accordingly, we found that their thermal safety margin (TSM = 3.57 °C) and warming tolerance index (WT = 8.8) were notably lower than reported in others liolaemid lizards from cold temperate environments such as Phymaturus tenebrosus (TSM = 15.58 and WT = 23.3 86 ) and P. calcogaster (TSM = 3.98 °C and WT = 10.67 °C 87 ). Therefore, these observations suggest that L. montanezi has a narrow TSM range to prevent it from reaching lethal temperatures 45 .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…At least a third (33%) of the recorded T e values were higher than the T pref during the warmest hours which increases the risk for these lizards of attaining near-lethal body temperatures close to their CT max . Accordingly, we found that their thermal safety margin (TSM = 3.57 °C) and warming tolerance index (WT = 8.8) were notably lower than reported in others liolaemid lizards from cold temperate environments such as Phymaturus tenebrosus (TSM = 15.58 and WT = 23.3 86 ) and P. calcogaster (TSM = 3.98 °C and WT = 10.67 °C 87 ). Therefore, these observations suggest that L. montanezi has a narrow TSM range to prevent it from reaching lethal temperatures 45 .…”
Section: Discussioncontrasting
confidence: 52%
“…The lizards were placed individually in a 2 °C chest refrigerator with glass-top door cooled at constant rate (approximately, − 0.7 °C/30 s). During cooling, the lizards were turned onto their back (no more than four times per individual) until they reached CT min , considered as the T b at which the lizard was no longer able to right itself when placed on its back 86 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2005), P. tenebrosus (26.3°C, Cabezas‐Cartes et al . 2019) and P. zapalensis (Ibargüengoytía et al . 2008; Duran et al .…”
Section: Discussionunclassified
“…A similar prediction has been formulated for P. tenebrosus (Cabezas‐Cartes et al . 2019) and other temperate‐environment lizards from Europe such as Z. vivipara (Chamaillé‐Jammes et al . 2006) Podarcis muralis (Deutsch et al .…”
Section: Discussionmentioning
confidence: 99%